2012
DOI: 10.1002/pros.22600
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of miR‐153 promotes cell proliferation via downregulation of the PTEN tumor suppressor gene in human prostate cancer

Abstract: Taken together, our results suggest that miR-153 play an important role in promoting proliferation of human prostate cancer cells and present a novel mechanism of microRNA-mediated direct suppression of PTEN expression in prostate cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 39 publications
5
69
1
Order By: Relevance
“…Cip1 (22). However, the underlying mechanism that modulates the abundance of the cyclins and CDKs in glioma has yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Cip1 (22). However, the underlying mechanism that modulates the abundance of the cyclins and CDKs in glioma has yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione peroxidase-3 acts as a tumor suppressor, and it is lost during PCa progression (141). miR-153 is another oncogenic miRNA that reportedly contributes to PCa progression through direct regulation of PTEN and FOXO1, and activation of the AKT pathway (142).…”
Section: Other Oncogenic Mirnasmentioning
confidence: 99%
“…An increasing number of studies have shown that miRNAs may not only play a significant role in PCa progression (6,7) such as proliferation (7), the cell cycle (8), apoptosis (9), invasion and metastasis (10)(11)(12) but also function as tumor suppressors or oncogenes depending on the genes that they regulate (13).…”
Section: Introductionmentioning
confidence: 99%